2023
DOI: 10.3389/fpls.2023.1147019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of “Green Revolution” gene Rht-B1b on coleoptile length of wheat

Abstract: Wheat coleoptile is a sheath-like structure that helps to deliver the first leaf from embryo to the soil surface. Here, a RIL population consisting of 245 lines derived from Zhou 8425B × Chinese Spring cross was genotyped by the high-density Illumina iSelect 90K assay for coleoptile length (CL) QTL mapping. Three QTL for CL were mapped on chromosomes 2BL, 4BS and 4DS. Of them, two major QTL QCL.qau-4BS and QCL.qau-4DS were detected, which could explain 9.1%–22.2% of the phenotypic variances across environments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…For instance, genes such as Rht1 and Rht2, as reported by Rebetzke et al [13], reduce both coleoptile length and plant height. In the conducted QTL analysis by Xu et al [14], it was demonstrated that the identified QTLs, QCL.qau-4BS and QCL.qau-4DS, could account for 9.1-22.2% of phenotypic variations in different environments at the Rht-B1 and Rht-D1 loci, respectively. Following transcriptome studies, the researchers identified several key pathways involving the function of Rht-B1b in coleoptile development, including phytohormones, circadian rhythm, and starch and sucrose metabolism [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, genes such as Rht1 and Rht2, as reported by Rebetzke et al [13], reduce both coleoptile length and plant height. In the conducted QTL analysis by Xu et al [14], it was demonstrated that the identified QTLs, QCL.qau-4BS and QCL.qau-4DS, could account for 9.1-22.2% of phenotypic variations in different environments at the Rht-B1 and Rht-D1 loci, respectively. Following transcriptome studies, the researchers identified several key pathways involving the function of Rht-B1b in coleoptile development, including phytohormones, circadian rhythm, and starch and sucrose metabolism [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the conducted QTL analysis by Xu et al [14], it was demonstrated that the identified QTLs, QCL.qau-4BS and QCL.qau-4DS, could account for 9.1-22.2% of phenotypic variations in different environments at the Rht-B1 and Rht-D1 loci, respectively. Following transcriptome studies, the researchers identified several key pathways involving the function of Rht-B1b in coleoptile development, including phytohormones, circadian rhythm, and starch and sucrose metabolism [14]. In other studies, it has been reported that Rht-B1b may reduce wheat coleoptile length (CL), but molecular-level investigations were lacking.…”
Section: Introductionmentioning
confidence: 99%